2019
DOI: 10.11648/j.plant.20190702.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Planting Date and Different Inorganic NP Fertilizer Rates for Irish Potato (<i>Solanum tuberosum L.</i>) Production at Bore, Southern Ethiopia

Abstract: The experiment was conducted at Bore Agricultural Research Center on station for three consecutive years' main cropping seasons with the aim to adjust planting date and fertilizer rate for Irish Potato production. Four level of fertilizer rate (0, 61.5, 82, and 114 kg Nitrogen and 0, 69, 92, and 115kg P ha-1 and planting date Immediately rain season (T1), 7days after rain (T2), 15days after rain (T3), 3 weeks later (T4). The treatments were arranged in RCBD in factorial arrangement with 3 replications. Tubers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…This result was lower than the study of Korji and Kebede (2017) who harvested 26.6t/ha from Gudane variety. In addition, the result of Tilahun (2018) showed that from Gudane 40.72 t/ha and Teshome et al, (2023) reported 23.59 t/ha of Zemen was harvested. The finding of this study was higher than the results of Dembi et al, (2020) and ESS (2022) where Gudane variety can gave 14.9 t/ha at highlands of Guji zone and the national yield of potato was 16.68 t/ha respectively.…”
Section: Yield Performance Of Potato Varietiesmentioning
confidence: 98%
“…This result was lower than the study of Korji and Kebede (2017) who harvested 26.6t/ha from Gudane variety. In addition, the result of Tilahun (2018) showed that from Gudane 40.72 t/ha and Teshome et al, (2023) reported 23.59 t/ha of Zemen was harvested. The finding of this study was higher than the results of Dembi et al, (2020) and ESS (2022) where Gudane variety can gave 14.9 t/ha at highlands of Guji zone and the national yield of potato was 16.68 t/ha respectively.…”
Section: Yield Performance Of Potato Varietiesmentioning
confidence: 98%